ANALISIS YURIDIS TERHADAP MENINGGALNYA MUDHARIB DALAM AKAD PEMBIAYAAN MUDHARABAH PADA PERBANKAN SYARIAH - Irawan, Vendra (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
AbstractThe purpose of this research is to examine the legal consequences of the death the capital manager (mudharib) in the mudharabah financing contract. The type of research used is normative juridical with a statute approach and a conceptual approach. The sources of legal material in this study are from primary legal material and secondary legal material. The results of the analysis of this study are that when the capital manager dies in the mudharabah financing contract in Islamic banking, the agreement made between the capital owner and the capital manager ends automatically. The point is that the legal relationship between the capital owner and the capital manager has been broken up since then and has also resulted in the breaking up of rights and obligations among the parties that made the agreement. While all forms of risk in the mudharabah contract are borne by the owner of the capital, unless the capital manager is proven to have made a deliberate mistake, negligent or violated the agreement. Since the capital manager has died in the mudharabah financing contract, the capital owner may not sue his familys to pay the remaining payment from the financing because mudharabah is not a debt agreement. To restore the capital, the owner of the capital that has not been paid by the deceased capital manager is to sell his capital management business, or if the business is still running, the familys may continue the business of the deceased capital manager with the agreement of the capital owner.